Inovasi Pembelajaran Bahasa dengan Metode Sugestopedia - Hemas Haryas Harja Susetya; Diana Nafisa (Fakultas Sains dan Teknologi Universitas Kanjuruhan Malang, 2024)
Abstract. This study examines the implementation of the suggestopedia method in Indonesian language learning at the Indonesian Language Education Study Program, Islamic University of Zainul Hasan Genggong Probolinggo. Utilizing a qualitative approach with action research methodology, this study involved 5 lecturers and 50 students over one semester. The results show significant improvements in student motivation and confidence, with a decrease in language anxiety from 65% to 30%. Students' language proficiency increased, with an average improvement of 28% in speaking skills and 22% in writing skills. Long-term retention of learning materials improved by 40% compared to conventional methods. Implementation challenges included initial adaptation by lecturers and students, resource limitations, and integration with existing curricula. The study also revealed positive impacts on lecturers' professional development, with 80% reporting increased creativity and teaching motivation. These findings have important implications for curriculum development and language education policies in higher education. Further research is needed to explore the long-term impacts and potential for wider application of the suggestopedia method.